2013
DOI: 10.1590/brag.2013.038
|View full text |Cite
|
Sign up to set email alerts
|

Depressão endogâmica e heterose de híbridos de populações F2 de milho no estado de São Paulo

Abstract: A heterose e a depressão por endogamia são fenômenos complementares importantes nas estratégias de melhoramento, como para a obtenção de híbridos convencionais e melhoramento de populações. Este trabalho teve por objetivos avaliar híbridos de populações F 2 de milho quanto aos caracteres agronômicos, estimar a heterose em relação à média dos pais e determinar a depressão endogâmica na obtenção das populações de genitores F 2 . Foram avaliados 10 híbridos de populações F 2 , cinco populações de genitores F 2 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
3
7
0
2
Order By: Relevance
“…Still, such hybrids showed high estimates of û + â, qualifying them to compose populations source of superior lines for GY (Table 4). The results coincide with studies that show a wide variation in the levels of inbreeding depression for grain yield in corn (Bernini & Paterniani, 2012;Bernini et al, 2013;Pacheco et al, 2002). This variation stems from differences in the levels of dominance between the traits, different allele frequencies and degree of relatedness between individuals in the population (Hallauer et al, 2010).…”
Section: Resultssupporting
confidence: 88%
“…Still, such hybrids showed high estimates of û + â, qualifying them to compose populations source of superior lines for GY (Table 4). The results coincide with studies that show a wide variation in the levels of inbreeding depression for grain yield in corn (Bernini & Paterniani, 2012;Bernini et al, 2013;Pacheco et al, 2002). This variation stems from differences in the levels of dominance between the traits, different allele frequencies and degree of relatedness between individuals in the population (Hallauer et al, 2010).…”
Section: Resultssupporting
confidence: 88%
“…The authors observed that specific hybrid combinations overcame the means of the witnesses and the means of the populations in question, demonstrating the potential of the genotypes in the production of intermediate hybrids. Similar results were obtained by Carvalho et al (2004), Garbuglio and Araújo (2006), Santos (2009), Bernini and Paterniani (2012) and Bernini et al (2013).…”
Section: Pfann Et Al (2009) Verified For Grain Yield Thatsupporting
confidence: 89%
“…also explained by the good combining ability between its parents, in which each parent had favorable complementary genes with the other parent (Bernini et al, 2013). With regard to progeny 81, because it is a progeny originated by self-pollination, which provides the highest level of homozygousness, their grain yield is somewhat surprising, since its productivity was about six times the national average of the 2005/2006 crop (714 kg ha -1 , CONAB, 2017), however as castor bean is a kind of reproduction type taken as mixed, may have decreased the deleterious effects deriving from the increase of homozygosity.…”
Section: Continuaçãomentioning
confidence: 99%
“…Rev. Ceres, Viçosa, v. 67, n.1, p. 042-051, jan/feb, It can be observed that of the more stable preselected progenies, are from free pollination and the other 9 from cross-pollination, can these 9 progenies of crosspollination resulting in highly productive hybrids (Bernini et al, 2013).…”
Section: Continuaçãomentioning
confidence: 99%